PROSES PENYIDIKAN TERHADAP TINDAK PIDANA YANG DIDUGA DILAKUKAN OLEH ORANG YANG MEMPUNYAI GANGGUAN JIWA - Nurhalimah Fair; Muin Fahmal; Abdul Agis (Qawanin Jurnal Ilmu Hukum, 2020)
This study aims to determine the steps taken by investigators against criminals who have mental disorders and to find out further legal proceedings against criminal offenders who have mental disorders. This research method uses data collection techniques by means of empirical research. The research was conducted in Makassar, namely at the Makassar POLRESTABES. The results of this study indicate that the steps taken by investigators against perpetrators of criminal acts who have mental disorders are interviews at the examination and observation stages. Then corresponded to Dadi Makassar Hospital to carry out an examination of the perpetrators as stated in the Visum et Repertum Psychiatricum letter, whose core conclusion states whether the examinee has mental disorders or does not have mental disorders. And the legal process against the perpetrator who is suspected of having a mental disorder, that is, if proven, the perpetrator is freed from all legal charges (SP3), if it is not proven that he has a mental disorder, the legal process will continue so that the perpetrator is held accountable for his actions.